Recurrent Pericarditis in Myhre Syndrome1. Issue 5 (22nd April 2013) - Picco, Paolo; Naselli, Aldo; Pala, Giovanna; Marsciani, Alberto; Buoncompagni, Antonella; Martini, Alberto
Abstract Myhre syndrome is a rare disorder characterized by pre‐ and postnatal short stature, brachydactyly, facial dysmorphism (short palpebral fissures, maxillary hypoplasia, prognathism and short philtrum), thick skin, muscular‐appearing body build, decreased joint mobility, mixed hearing loss, and cleft lip and palate. Other clinical features include skeletal dysplasia, developmental delay with intellectual disability and/or behavioral disturbance, cardiac defects, cryptorchidism, and bone anomalies. The disease is caused by recently identified SMAD4 mutations. Here we describe a 7‐year‐old boy with a molecularly proven Myhre syndrome who presented life‐threatening recurrent pericarditis and systemic inflammatory symptoms that required treatment with steroid and recombinant interleukin‐1 receptor antagonist.